On the successive Kings’ preferential treatment for Chinese in the Monarchical Period of Chakri Dynasty (1782-1932) - Chen, K (Huachiew Chalermprakiet University, 2020)
Based on the Chinese materials, this article explores the successive kings’ preferential treatment for Chinese in the monarchical period of Chakri Dynasty (1782-1932).